A carbon-carbon hydrolase from human gut probiotics Flavonifractor plautii catalyzes phloretin conversion. (December 2022) - Qiu, Ting Yuan; Gong, Tian; Zhang, Shuai; Chen, Qi Hang; Hu, Ching Yuan; Meng, Yong Hong
Abstract: Although the catabolic pathway of some flavonoids in the human colon has been elucidated, knowledge of related gut microbes and responsible enzymes is still limited. In this study, a phloretin hydrolase gene ( phy ) from Flavonifractor plautii ( F. plautii ) was synthesized and heterologously expressed in Escherichia coli BL21 ( E. coli BL 21). Phloretin hydrolase (PHY) was purified from cell extracts of recombinant E. coli BL21, and PHY's molecular weight was about 32 kDa. The purified PHY effectively cleaved phloretin into 3-(4-hydroxyphenyl) propionic acid (HPPA) and phloroglucinol (PG). PHY's kinetic parameters were determined: K m was 2.8 × 10 −3 ±0.4 mM and V max was 411.2 ± 7.1 U/mg. Besides, PHY's optimal temperature and pH were 50 °C and 7.5, respectively, and PHY exhibited 75% activity after 5 h at 50 °C. Furthermore, PHY's activity was inhibited in the presence of Ba 2+, Cu 2+, and Fe 2+, while Mg 2+ slightly elevated PHY's activity. Finally, the catalytic model between phloretin and PHY was built using molecular docking, and PHY's conformational changes were further demonstrated through the multispectral techniques. This study is conducive to understanding phloretin metabolism in the colon and adding a valuable source of PHY for food industry application. Highlights: F. plautii 's phloretin hydrolase (PHY) was expressed, purified, and characterized. F. plautii 's PHY exhibited excellent catalytic efficiency to phloretin. The optimal pH and temperature of F. plautii 's PHY were 7.5 and 50 °C. Phloretin binds effectively to the active catalytic sites of F. plautii 's PHY. F. plautii is a valuable source of PHY for application in the food industry.